Effects of zinc, boron and sulfur on grain yield, activity of some antioxidant enzymes and fatty acid composition of rapeseed (Brassica napus L.) - Tayebeh SHOJA; Majid MAJIDIAN; Mohammad RABIEE (Acta Agriculturae Slovenica)
A field experiment was conducted to study the effects of elements zinc (Zn), boron (B) and sulfur (S) and their interactions on quantitative and qualitative agronomic characteristics of rapeseed. Minimum grain oil and seed yield were obtained from control treatments and the highest seed yield were obtained from S + B + Zn treatments. The maximum of oleic acid (229.6 mg g-1) and linolenic acid (27.14 mg g-1) were obtained from B + Zn + S treatment. Maximum of linoleic acid (55.55 mg g-1) were obtained from B + Zn treatment. However, the highest superoxide dismutase activity was obtained from S + B + Zn treatments 10.24 unit mg-1 and the highest peroxidase activity were obtained from Zn treatment 0.87 µmol g-1 FM min. Regard to this experiment results, application of B, S and Zn fertilizers with NPK fertilizer can help to increase the yield and yield components in rapeseed. Also fatty acids composition of rapeseed are influenced by nutrients and since quality of edible oils depends on unsaturated fatty acids, especially linoleic and linolenic acids and these acids are essential fatty acids for the human body that must be supplied through diet. Therefore this research showed that we are not only able only to increase oil yield but also oil quality with desired fatty acid composition.